EU Merger Remedies: A Preliminary Empirical Assessment - Tomaso Duso; Klaus Gugler; Burcin B. Yurtoglu (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
Mergers that substantially lessen competition are challenged by antitrust authorities. Instead of blocking anticompetitive transitions straight away, authorities might choose to negotiate with the merging parties and allow the transactions to proceed with modifications that restore or preserve the competition in the involved markets. We study a sample of 167 mergers that were under the European Commission's scrutiny from 1990 to 2002. We use an event study methodology to identify the potential anticompetitive effects of mergers as well as the remedial provisions on these transactions. Stock market reactions around the day of the merger's announcement provide information on the first question, whereas the stock market reactions around the commission's final decision day convey information about the outcome of the bargaining process between the authority and the merging parties. We first classify mergers according to their effects on competition and then we develop hypotheses on the effects that remedies are supposed to achieve depending on the merger's competitive outcome. We isolate several stylized facts. First, we find that remedies were not always appropriately imposed. Second, the market seems to be able to predict remedies' effectiveness when applied in phase I. Third, the market also seems able to produce a good prior to phase II's clearances and prohibitions, but not to remedies. This can be due either to a measurement problem or related to the increased merging firms' bargaining power during the second phase of the merger review.
urn:nbn:de:bvb:19-epub-13470-9
Keywords: L4; K21; C12; C13; 330; Merger Control; Remedies; European Commission; Event Studies